Splicing thermotolerance maintains pre-mRNA transcripts in the splicing pathway during severe heat shock. - Corell, R.A.; Gross, R.H. (Experimental Cell Research, 1992)
Thermotolerance, the ability of cells and organisms to withstand severe elevated temperatures after brief exposure to mild elevated temperatures, has been studied in numerous laboratories. Survival thermotolerance is defined as the increase in cell or organism survival at severe elevated temperatures after a pretreatment at mild elevated temperatures. This study examines splicing thermotolerance in Drosophila melanogaster, the ability to splice pre-mRNAs made at the severe temperature (38 degrees C) after a brief pretreatment at a milder temperature (35 degrees C). It is probably one of a number of mechanisms by which cells adapt to heat shock. These experiments demonstrate that pre-mRNAs synthesized at the severe temperatures in splicing thermotolerant cells, although protected in splicing-competent complexes, are not actually processed to mature mRNAs until the cells are returned to their normal temperature. We have also studied the kinetics of acquisition and loss of splicing thermotolerance. As little as 10 min of pretreatment at 35 degrees C was sufficient to provide full splicing thermotolerance to a 30-min severe heat shock of 38 degrees C. Pretreatments of less than 10 min provide partial splicing thermotolerance for a 30-min severe heat shock. Full splicing thermotolerance activity begins to decay about 4 h after the cessation of the 35 degrees C incubation and is completely lost by 8 h after the pretreatment. The kinetics experiments of pre-mRNAs synthesized during the 38 degrees C treatment in splicing thermotolerant cells indicate that one or more splicing thermotolerance factors are synthesized during the 35 degrees C pretreatment which interact with pre-mRNA-containing complexes to keep them in a splicing-competent state. These kinetic experiments also indicate that in cells which are partially splicing thermotolerant, the pre-mRNAs synthesized early during the 38 degrees C incubation are protected, whereas those synthesized late are not. In the absence of splicing thermotolerant factors, the pre-mRNA-containing complexes leave the normal splicing pathway and are allowed to exit to the cytoplasm.